Development of a Google Sites-Based Literacy Movement Program in Elementary Schools - Isuharni Binte Idris; Muhammad Hanafi; Aswadi; Syamsu T; Jumiati; Jamaluddin Ahmad (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study developed and evaluated the effectiveness of a Google Sites-based School Literacy Movement (GLS) program to improve reading comprehension skills among fifth-grade students at UPT SD Negeri 1 Rijang Panua, Indonesia. The research was driven by the moderate literacy achievement of 55.33% reported in the 2024 Education Report, stemming from suboptimal GLS implementation that emphasized routine reading without structured comprehension assessment and relied on conventional, less engaging media. Employing a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study produced “SIBACA SITES” (Smart Reading System Based on Google Sites), an interactive web-based platform integrating contextual reading texts, multimedia resources, comprehension exercises, and interactive features. Expert validation by material, media, instructional design, and language specialists yielded very high feasibility scores (89%, 91%, 92%, and 91%, respectively), placing the product in the “very feasible” category. Limited trials (n=10) resulted in an average N-gain score of 0.60 (moderate effectiveness), while extensive trials (n=25) demonstrated more substantial gains: 16 students in the moderate category and 9 in the high category, with no students in the low category. Questionnaire responses from students and teachers indicated highly positive perceptions regarding attractiveness, usability, and learning benefits. The findings confirm that the Google Sites-based GLS program is valid, practical, and effective in enhancing reading comprehension. Theoretically, it strengthens digital literacy, multimodal literacy, and constructivist learning principles. Practically, it offers an innovative, technology-integrated model for implementing the School Literacy Movement in elementary schools, supporting 21st-century competencies.